Conditions of Comprehensiveness and Distinction in Juristic Definitions - Al-Omar, Amal Tariq (Journal of Islamic Sciences, 2024)
The objection to the limit by distorting the condition of inclusion and exclusion is one of the most significant criticisms in definitions. It aims to prevent the definition from clearly identifying individuals within the defined group, thereby allowing some individuals to exit the definition or others of a different category to enter. This objection falls under the objection by negation, leading to the nullification of the definition. Many juristic definitions are not immune to this objection, prompting this study to clarify the meaning of the condition of equivalence in definitions, known as the condition of "inclusion and exclusion," and to outline its application constraints according to jurists using an analytical-inductive approach. The first part of the study provides a brief explanation of the meanings of "definition" and "limit," and the meaning of "definition by description." It then discusses the conditions of definitions, categorizing them into those pertaining to meaning and those pertaining to wording. In the second part, it explores the meaning of the condition of inclusion and exclusion, and the opinions of scholars regarding its application whether absolute in every definition or restricted. The focus is on the perspectives of jurists. It concludes by highlighting the primary reasons for objecting to juristic definitions by negation, providing examples and responses. The research concludes with several findings, notably that the condition of inclusion and exclusion is not universally applied in formal definitions as mentioned by jurists, but rather it is restricted by conditions such as the negated category not being abnormal or rare, its exclusion due to a distortion of the condition, or the presence of a preventive factor that excludes it from being considered within the defined group.